2015
DOI: 10.1039/c5ra02708j
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bimodal thermally-induced denaturation of type I collagen extracted from calfskin

Abstract: DSC tracks of collagen in solution revealing a bimodal behaviour during its heat-induced denaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 97 publications
(133 reference statements)
3
8
0
Order By: Relevance
“…In addition, a secondary exothermal peak (32.9 ± 0.31 °C) was identified in the DSC thermogram (Figure 3B). It was consistent with our observation on the viscosity changes in T. flavidus collagen (Figure 3A), indicating a partial denaturation of collagen supramolecular structure due to defibration of thermally unstable hydroxyproline-free sequence in collagen triple helices [28].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, a secondary exothermal peak (32.9 ± 0.31 °C) was identified in the DSC thermogram (Figure 3B). It was consistent with our observation on the viscosity changes in T. flavidus collagen (Figure 3A), indicating a partial denaturation of collagen supramolecular structure due to defibration of thermally unstable hydroxyproline-free sequence in collagen triple helices [28].…”
Section: Resultssupporting
confidence: 92%
“…They have been reported to decrease the entropic cost of collagen folding by preorganizing individual poly-Pro II chain [27]. They can also stabilize collagen triple helices via interchain hydrogen bond through hydroxyl groups [28]. The content of imino acids is therefore an important factor modulating collagen thermal stability [27,29].…”
Section: Resultsmentioning
confidence: 99%
“…Thermograms for each collagen sample are shown in Figure . NC shows two characteristic peaks that were consistently observed in NC denaturation—a minor peak at 32–33°C and a major peak at 38–40°C, confirming the bimodal collagen denaturation observed by others . Data for denaturation temperature and enthalpy for all CO 2 ‐treated samples is shown in Table .…”
Section: Resultssupporting
confidence: 82%
“…The sample thermogram for NC‐U in Figure a suggests a bimodal denaturation process; this was also observed recently by Staicu et al under similar conditions. The smaller initial peak is caused by the disassembly of supramolecular complexes (that is, separation of different collagen molecules from each other) and the large second peak indicates the unfolding of each individual triple helical collagen molecule into a random coil formation.…”
Section: Discussionsupporting
confidence: 86%
“…The DSC curves show that every collagen samples exhibited a characteristic thermal denaturation peak. The minor endothermic peak (Tm 1 ) at low temperature was owing to a breakage of hydrogen bonds in the aggregates of collagen, which was apt to be neglected, and the major endothermic peak (Tm 2 ) at high temperature was initiated by the transition of triple helix to the random coil state [37,38]. Compared with Col, the thermal denaturation temperature of Col/ILs-soluble70% was reduced by 7.63°C, which is larger than the decrease of Colregenerated-35°C with 4.1°C reported by Hu et al [22] This showed the thermal stability decreased more significantly with [EMIM][Ac] concentration.…”
Section: Thermal Analysis Of Soluble Collagenmentioning
confidence: 99%